1992
DOI: 10.1007/bf00182423
|View full text |Cite
|
Sign up to set email alerts
|

Absolute curvature measures, II

Abstract: The absolute curvature measures for sets of positive reach in R d introduced in [7] satisfy the following kinematic relations: Their integrated values on the intersections with (or on the tangential projections onto) uniformly moved p-planes are constant multiples of the corresponding absolute curvature measures of the primary set. In the special case of convex bodies the first result is the so-called Crofton formula. An analogue for signed curvature measures is well known in the differential geometry of smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
(12 reference statements)
0
10
0
Order By: Relevance
“…Then nor X is H' l~l -measurable and locally (d -l)-integrable and, at H d~lalmost all (x. n) e nor X, the (generalized) principal directions a,(x,ri) e S d~l and (generalized) principal curvatures K,(X, ri) e (-00, 00] (/ = 1,..., d -1) are denned so that the (H''~\d -l)-approximate tangent cone Tan''" 1 (nor X, (x, ri)) is a {d -1 )-dimensional linear subspace of K 2 '' spanned by the vectors Remark. The analogous result for sets with positive reach was stated and used in [10]. We present a proof here for the sake of completeness.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“…Then nor X is H' l~l -measurable and locally (d -l)-integrable and, at H d~lalmost all (x. n) e nor X, the (generalized) principal directions a,(x,ri) e S d~l and (generalized) principal curvatures K,(X, ri) e (-00, 00] (/ = 1,..., d -1) are denned so that the (H''~\d -l)-approximate tangent cone Tan''" 1 (nor X, (x, ri)) is a {d -1 )-dimensional linear subspace of K 2 '' spanned by the vectors Remark. The analogous result for sets with positive reach was stated and used in [10]. We present a proof here for the sake of completeness.…”
mentioning
confidence: 61%
“…(Note that, in particular, any set from the convex ring is a UPR set.) The definition presented extends that of Zahle [10,13] by considering the index function of UPR sets. It is shown that the Crofton intersection formula for absolute curvature measures is still valid for UpR-sets; this is achieved by generalizing a translative intersection formula for sets with positive reach [6].The definition presented makes it possible to compare the two approaches appearing in the literature and mentioned above to define non-negative variants of intrinsic volumes and curvature measures, namely, that of Matheron and Schneider with the integral-geometric one (Santalo, Baddeley, and Zahle), since the system of locally finite unions of convex bodies is covered by both of them.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Let us fix a convex body K ∈ K d and some [51], [18], [54], [35], [44] have introduced naturally defined measures. For convex bodies, however, all these measures are essentially equivalent.…”
Section: Notation and Statement Of Resultsmentioning
confidence: 99%
“…2. A parametrization of this rectifiable set is provided in [54] and [35]. We say that K is supported from outside by an orthogonal spherical cylinder at E ∈ A (K, d, r) if there is some R > 0 and some…”
Section: Lemma 43 Letmentioning
confidence: 99%